1968
DOI: 10.1172/jci105864
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone hypersecretion in “non-salt-losing” congenital adrenal hyperplasia

Abstract: A B S T R A C T Patients with the "non-salt-losing" form of the adrenogenital syndrome were studied before and after suppression of adrenal cortical activity with carbohydrate-active steroids. The response of aldosterone secretion to sodium deprivation was measured; in some patients response to adrenocorticotropic hormone (ACTH) was measured as well.The aldosterone secretion was normal and responded normally to sodium deprivation in all patients studied during suppression with carbohydrate-active steroids. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The ASR values of our six children can be regarded as on the high side. Above normal values for ASR in nonsalt losers have also been found in two of three cases by JAILER et al [23], and high values have also been reported by Ko-WARSKI et al [25] and by BARTTER et al [3].…”
Section: Loras Haour and Bertrandsupporting
confidence: 58%
See 3 more Smart Citations
“…The ASR values of our six children can be regarded as on the high side. Above normal values for ASR in nonsalt losers have also been found in two of three cases by JAILER et al [23], and high values have also been reported by Ko-WARSKI et al [25] and by BARTTER et al [3].…”
Section: Loras Haour and Bertrandsupporting
confidence: 58%
“…They showed a response to ACTH with an increase in cortisol secretion, but this response was invariably less than normal. 24 Na excreted in the urine in 24 h. 3 Interval between cessation of treatment and the start of the investigation.…”
Section: Cortisol Secretion Rates (Csr)mentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with the simple virilizing, non-salt-loosing form, 17a-OH-P concentration reaches 70 -240 nmol/l and in patients with the salt-loosing form 400 -1000 nmol/l (32,50). Regarding these high concentrations of 17a-OH-P, the anti-MC potency of 17a-OH-P, shown in this study, and the known antagonist effect of progesterone, give an explanation for the compensatory hyperaldosteronism in patients with the simple virilizing form (28,51). The salt wasting is probably due to the complete lack of 21-hydroxylase activity and of aldosterone and cortisol production.…”
Section: Progesterone and Hmrsupporting
confidence: 53%